2018
DOI: 10.3389/fmolb.2018.00065
|View full text |Cite
|
Sign up to set email alerts
|

How Does Solvation Layer Mobility Affect Protein Structural Dynamics?

Abstract: Solvation is critical for protein structural dynamics. Spectroscopic studies have indicated relationships between protein and solvent dynamics, and rates of gas binding to heme proteins in aqueous solution were previously observed to depend inversely on solution viscosity. In this work, the solvent-compatible enzyme Candida antarctica lipase B, which functions in aqueous and organic solvents, was modeled using molecular dynamics simulations. Data was obtained for the enzyme in acetonitrile, cyclohexane, n-buta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 92 publications
3
55
0
Order By: Relevance
“…In previous studies, similar behavior was found for Candida rugose lipase (CRL) that CCl4 rendered the side chains in the hydrophobic substrate binding site of CRL more mobile . These results also confirmed that local protein dynamics are associated with solvents interaction . Thereby, except inhibition and water stripping off, the conformational change caused by the interaction of OSs with residues in the substrate binding cleft could also be another main factor that influences the enzyme activity …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In previous studies, similar behavior was found for Candida rugose lipase (CRL) that CCl4 rendered the side chains in the hydrophobic substrate binding site of CRL more mobile . These results also confirmed that local protein dynamics are associated with solvents interaction . Thereby, except inhibition and water stripping off, the conformational change caused by the interaction of OSs with residues in the substrate binding cleft could also be another main factor that influences the enzyme activity …”
Section: Discussionsupporting
confidence: 81%
“…Enzymes generally require some essential water molecules bound to the surface of enzymes to maintain protein structure, dynamics, and function . The addition of water molecules can increase both the kinetics and flexibility of enzymes in OSs . Although water activity (a w ) is an important experimental factor for enzyme activity in non‐aqueous media (e. g., pure OSs), however, it is challenging to predict critical hydration level in polar OSs .…”
Section: Discussionmentioning
confidence: 99%
“…Regional differences in hydration dynamics around the protein surface have been connected with molecular recognition events within the protein. The tie between local solvent dynamics and regional protein dynamics (flexibility/stability) may explain protein conformational states, which are dependent on a measure of the local hydration and friction/viscosity parameters [ 52 ].…”
Section: The Primary Secondary and Tertiary Structures Of Sars-comentioning
confidence: 99%
“…At some point, the free energy change is sufficiently negative and stable so that the mAb and the receptor can enter an “induced fit”, during which their conformations change in a coordinated way, to reach an optimal negative free energy. The “induced fit” process is intimately coupled to solvation water dynamics [ 18 ]. Most likely solvation water dynamics is also involved in the process of “sampling the free energy landscape” [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%